THE INFLUENCE OF TRUST AND INFORMATION QUALITY ON ONLINE PURCHASE DECISION IN THE SHOPEE APPLICATION (A CASE STUDY ON PT SRI BOGOR’S EMPLOYEE) - Esa Indra Mustika; Antoni Ludfi Arifin (International Journal of Social Science, 2021)
This study aims to determine how trust and information quality influence online purchasing decisions for Shopee application users. This research is a quantitative study with trust, information quality, and purchase decisions as variables. The population of this research was employees of PT SRI Bogor, who had at least used the Shopee application once. The sample used in this study consisted of 90 respondents who were taken using the accidental sampling technique. Data collection was carried out using questionnaires, in which each respondent was given 25 statements. The data were then analyzed using regression analysis techniques, classical assumption tests, and hypothesis testing. The results of this study indicate that: (1) Trust has a positive effect on purchasing decisions with a value of 28%; (2) Quality of information has a positive effect on purchasing decisions with a value of 37.4%; (3) Trust and quality of information simultaneously influence purchasing decisions with a value of 43.4%, while the remaining 56.6% is influenced by other variables not examined.